MAIN METHODS OF CONCEPTUAL RESEARCH IN LINGUISTICS (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
Abstract. The current intensification of conceptual research in linguistics is explained by the fact that the concept has the potential to shed light on the pressing issue of the relationship between language and thinking in the social sciences, which has interested linguists since the 18th century.